Learning and instruction - European Association for Research on Learning and Instruction (Elsevier Science, 1991)
"Learning and Instruction is an international, multi-disciplinary journal that provides a platform for the publication of the most advanced high-quality research in the areas of learning, development, instruction and teaching."
Keywords: Learning : Periodicals; Teaching : Periodicals; Learning; Teaching